Achieving room temperature DNA amplification by dialling in destabilization1. Issue 44 (4th June 2015) - Alladin-Mustan, B. Safeenaz; Mitran, Catherine J.; Gibbs-Davis, Julianne M.
<x xml:space="preserve">Abstract</x> The ability to amplify nucleic acid sequences at room temperature without the need for any heating element has been achieved, which has promise in bio-diagnostics employed at the point of care.